2015
DOI: 10.1016/j.bbmt.2014.11.675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unrelated Cord Blood and Peripheral Blood Stem Cell Transplantation in Adults with Myelodysplastic Syndrome after Reduced-Intensity Conditioning Regimen: A Collaborative Study from Eurocord (Cord blood Committee of Cellular Therapy & Immunobiology Working Party of EBMT) and Chronic Malignancies Working Party

Abstract: Hematopoietic stem cell transplantation (HSCT) remains the only curative treatment in patients with higher risk myelodysplastic syndrome (MDS), but the choice of the optimal alternative stem cell source is still a subject of debate in patients lacking an HLA-matched sibling donor. Here, we report on a large series of patients with MDS (N = 631) transplanted either with mobilized peripheral stem cells (PBs) from unrelated donors (n = 502) or with umbilical cord blood transplant (UCB, n = 129) as alternative gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 18 publications
2
47
1
Order By: Relevance
“…The European Group for Blood and Marrow Transplantation (EBMT) reviewed a group of 129 patients with MDS that underwent UCBT, finding similar results with 2-year probabilities of chronic GVHD, relapse, TRM, DFS, and OS of 23%, 30%, 42%, 28%, and 30%, respectively [14]. One key difference between the two studies, is that a majority (71%) of the patients in the EMBT analysis had progressed to acute myeloid leukemia prior to transplantation, with less than half (48%) of them in remission prior to transplantation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The European Group for Blood and Marrow Transplantation (EBMT) reviewed a group of 129 patients with MDS that underwent UCBT, finding similar results with 2-year probabilities of chronic GVHD, relapse, TRM, DFS, and OS of 23%, 30%, 42%, 28%, and 30%, respectively [14]. One key difference between the two studies, is that a majority (71%) of the patients in the EMBT analysis had progressed to acute myeloid leukemia prior to transplantation, with less than half (48%) of them in remission prior to transplantation.…”
Section: Discussionmentioning
confidence: 93%
“…There have been few published series solely describing the outcomes of adult patients who have undergone UCBT for MDS [1214]. In the absence of substantial data, patients that could benefit from UCBT may not be offered the treatment option when they otherwise would be considered for matched related or unrelated donors.…”
Section: Introductionmentioning
confidence: 99%
“…8 The European Group for Blood and Marrow Transplantation (EBMT) has previously reported that HLAmismatched unrelated donors can give similar results to UCB donors in MDS patients, but worse outcomes than HLA-matched unrelated donors. 9 A recent Center for International Blood and Marrow Transplant Research (CIBMTR) study reported similar results in acute myeloid leukemia (AML) patients transplanted with haplo with PT-CY vs HLA-matched unrelated donors. 10 A similar comparison in patients with acute leukemia, MDS, chronic leukemia, or lymphoma has been done by Luo et al 11 showing equivalent outcomes for matched-related donors, HLA mismatched-unrelated donors, and haplos according to the Beijing protocol.…”
Section: Introductionmentioning
confidence: 89%
“…Based on these data, the authors concluded that PB MUD donors were the preferred stem cell source compared to UCB in the absence of a sibling donor. 26 While the outcomes of this study highlight a much larger “MDS” patient cohort, it is important to note that 65% of the MDS patients within the entire cohort had progressed to AML prior to transplantation and of those patients only 52% had achieved remission prior to transplant. Specifically within the UCB group 71% had progressed to AML and only 48% had achieved CR prior to transplant.…”
Section: Discussionmentioning
confidence: 89%
“…This study is thus limited by the heterogeneity of patients/conditioning regimens/supportive care inherent to a registry study and the small number of true MDS patients not progressing to AML receiving an UCB HCT (n=37). 26 Despite these limitations, the analysis importantly highlights surprisingly good outcomes of survival and relapse for such a high risk group of patients with the majority of the MDS patients progressing to AML, only half in remission, and receiving only RIC. Thus, these data suggest that both MUD/UCB RIC transplants can be effective in curing even high risk MDS/AML patients.…”
Section: Discussionmentioning
confidence: 99%